Antimicrobial susceptibility pattern of Escherichia coli and Klebsiella pneumoniae isolated from patients with urinary tract infections in a tertiary care hospital (Annals of Medical Research, 2021)
Aim: To determine etiological microorganisms from urine samples in patients diagnosed with UTI and to detect the antimicrobial susceptibility pattern of Escherichia coli and Klebsiella pneumoniae in a Tertiary Care Hospital.Materials and Methods: A cross-sectional study was conducted using urine culture samples and sensitivity reports collected retrospectively from our laboratory records over a period from Jan 2013 to Dec 2017.Results: A total of 729 urine culture isolates from 660 patients were included. Two-hundred eighty-four (41.8%) of the patients were male and 384 (58.2%) were female. The most common microorganisms were 46.4% E. coli, 18.2% K. pneumoniae and 12.1% Enterococcus spp., respectively. A total of 284 urine culture isolates produced extended spectrum beta-lactamases (ESBL), of which 186 (65.5%) were E. coli and 98 (34.5%) were K. pneumoniae. The most susceptible antimicrobials are meropenem, imipenem, amikacin, and fosfomycin, respectively. We determined that the antimicrobial drugs with the lowest susceptibility rates for both E. coli and K. pneumoniae were amoxicillin-clavulanate (24.5%), trimethoprim-sulfamethoxazole (30.7%) and ceftriaxone (43.2%). Additionally, their susceptibilities have gradually decreased. Ertapenem susceptibility has decreased more in K. pneumoniae isolates than E. coli.Conclusion: Antimicrobial resistance and ESBL-producing for both E. coli and K. pneumoniae have been increasing over the years. Our findings may contribute to choosing the proper antibiotic for the empirical treatment of UTI and preventing treatment failure.